Redistribution, Occupational Choice and Intergenerational Mobility: Does Wage Equality Nail the Cobbler to His Last? - Anna Sjögren (The Research Institute of Industrial Economics (IUI), 2000)
The classical Roy-model of selection on the labor market is extended in order to analyze intergenerational mobility. This is done by linking ability uncertainty to family background. I derive implications for the allocation of talent and for background dependent earnings patterns within occupations and show that a very compressed wage structure can cause negative sorting of people with family background in the occupation with low returns to ability. I also study the effects of income redistribution on mobility and talent allocation. It is found that a redistributive welfare system either reduces vertical mobility or enhances it at the cost of a shrinking proportion of people choosing the occupation with high returns.
Keywords: J62; J68; 330; Intergenerational mobility; Occupational choice; Allocation of talent; redistribution; Berufswahl; Familiensoziologie; Einkommensverteilung; Arbeitsmobilität; Theorie